(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Anemia is one of the nutritional problems that are often faced by adolescents, one of which is caused by iron deficiency. Anemia in adolescents adversely affects the decline in immunity, concentration, learning achievement, fitness, and productivity. The cause of anemia in adolescents is caused by rarely eating breakfast or frequently consuming foods or drinks that can inhibit the absorption of nutrients by the body such as caffeine, tannins, oxalates, and phytates, which are found in soybean, tea, and coffee products. Providing health counseling to adolescents about the fulfillment of iron and the selection of types of food or drinks that prevent anemia. Examination of hemoglobin levels aims to determine the incidence of anemia in adolescents. The target of this activity is class XI students of SMAIT Almumtaz Pontianak. This community service resulted in a change in the knowledge of students XI SMAIT Almumtaz from the results of the Pretest 75.8% of students had sufficient knowledge and 24.2% had good knowledge after health education about anemia obtained the post-test results 84.8% had good knowledge and 15.2% had sufficient knowledge, meaning that there was a change in the knowledge and understanding of students XI SMAIT Almumtaz. An overview of the Hb level of female students was obtained with the results of Hb more than equal to 12 scores (86.2%) and 13.8% Hb scores less than 12 male students and 100% of male students had Hb levels above more than equal 14. Keywords: Anemia, Hb, Adolescents.